Tourism Events and the Nature of Stakeholder Power - Tiew, F.; Holmes, Kirsten; De Bussy, Nigel (2015)
This exploratory case study examines the power relations among the stakeholders of a tourism event in Borneo. It examines the sources of stakeholder power and the pattern of interdependence of various stakeholders, primarily based on interviews with event managers and stakeholders, as well as field visits. An analysis of the different types and amount of resource control, dependency, and network centrality resulted in four different categories of stakeholder power patterns—executive, asset based, referral, and diffuse stakeholders. The study also found that resource-based power was the primary source of power, whereas network-based power was a secondary and supplementary source. The case study revealed that the salience of event stakeholders based on their power was highly variable due to the different types of power that they had. This article contributes to the literature of event tourism, a typology of the event stakeholder powers in a predominately government-owned music festival, and offered practical suggestions to event management. It also advances the stakeholder power concept within event tourism studies.